THE RELATIONSHIP BETWEEN RETAINING TALENT AND JOB SATISFACTION IN SELECTED PUBLIC UNIVERSITIES - M. Y., Kamal; Z. M., Lukman (International Journal For Research In Business, Management And Accounting, 2019)
Retaining Talent (RT) has turned into a basic issue to any associations. In higher education, to hold skillful, researchers and master are very hard in light of the fact that the mastery has by the academicians may most likely have started other universities to get them. On the other part, hold the best talent will build the Job Satisfaction (JS) of the university and because of that reason, it has activated Ministry of Higher Education (MOHE) to develop a couple of techniques on RT which turn into rules to the college to take after. Hence, this research is to distinguish the connection amongst's RT and JS in selected public university in Malaysia. Quantitative approach has been utilized as a part of the request to gather essential information from 238 respondents. Data acquired from this strategy has been examined utilizing IBM Statistical Package Social Sciences (SPSS). Therefore, there was a direct relationship recorded amongst RT and JS. Notwithstanding, University A scored marginally higher relationship amongst's RT and JS when contrasted with other two universities. In light of the discoveries got, the direct relationship shows that the college needs to enhance or rebuilt their projects, plot or methodologies on RT keeping in mind the end goal to support the JS of the establishments and in a roundabout way will accomplish the mission and vision of the college.